THE READINESS OF INTEGRATING SUSTAINABLE DEVELOPMENT INTO BIOLOGY TEACHER EDUCATION PROGRAM - Desa, Shakinaz; Abdullah, Mai Shihah; Ab Mutalib, Nurul Huda; Mansor, Rosnidar (Jurnal Cakrawala Pendidikan, 2021)
The idea of sustainability has long become a regulatory concept applied in national and international policies worldwide. This study aimed to investigate the understanding, attitude, and behavior levels towards education and sustainable development among key players in teacher education program, particularly in Biology, including learners, educators, administrators, and supporting personnel from the Biology Department of a public university in Malaysia. A set of validated questionnaires was administered online to 61 participants. A semi-structured interview was carried out with 9 randomly selected participants. An expert in the curriculum was referred to in search of integration of sustainable development in the current pro forma. Readiness was found highest in behavior, followed by both understanding and attitude. Courses in the Biology Teacher Education program need a well-planned integration to meet the sustainable development concept. Thus, we recommend readiness analysis as a part of the requirement in sustainable development-integrated curriculum design. The implication of this study is, a strategic action plan to interconnect the players’ readiness and curriculum design is a new imperative element in the teacher education program.